Settlement Preferences of Sea Cucumber, Bohadschia marmorata Jaeger. - Solidarios, Mey Neren Jane
In sea cucumber larvae development, they look for suitable substrate on which to settle and settlement cues play two important roles, one as a biological signal for the induction of larval metamorphosis, and another as a suitable food for settling juveniles. In recent studies higher mortality rates were noticed during larval metamorphosis and settlement stage. The effectiveness of eight different settlement cues was tested on competent Bohadschia marmorata doliolariae in a 108 hrs assay. Doliolarae metamorphosed ad settled in all cues even in negative control. Settlement response was rapid in treatments with Spirulina. At the 48th hour, Spirulina, Sargassum, Navicula and its combination have the same effect on inducing the settlement B. marmorata larvae. As the exposure to settlement cues were prolonged, Spirulina and combinations with it showed significant effect on the settlement of the larvae at 60th hour observation. Considering the mortality at the end of observation (108hr AS) there is no significant difference among the settled larvae exposed to the mixture of the three settlement cues, combinations of Spirulina (e.g. Spirulina+Sargassum, Spirulina+Navicula) and these groups were able to induce more B. marmorata larvae. In conclusion, Spirulina is the best method of quickly inducing larval settlement of B. marmorata. However, there must be provision of food to early settlers as well as ensure high survival after settlement